Job Satisfaction Judging from the Emotional Labor - Hartini, Sri; Chairani, Marina; Siregar, Melda Kristiani; Sipahutar, Putra Indo Sema (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2020)
AbstractÂ This study aims to determine whether there is a relationship between emotional labor and job satisfaction of teachers at the F. Tandean Tebing Tinggi college. The hypothesis is that there is a positive relationship between emotional labor and job satisfaction with teachers. The subjects of the study were 120 teachers in the School of F. Tandean Tebing Tinggi. This research uses quantitative research where the data collection uses a questionnaire. The assumption test consists of a normality test and a linearity test. The data analysis method used is the Product Moment correlation technique with the help of SPSS Statistics 25 for Windows. The results showed that there was a positive correlation between job satisfaction with emotional labor (Pearson Correlation 0.280, Sig 0.001 <p = 0.05). Contributions given emotional labor to job satisfaction amounted to 7.1 percent. The conclusion of this study is the research hypothesis in the form of a positive relationship between emotional labor and job satisfaction with teachers was accepted.AbstrakPenelitian ini bertujuan untuk hubungan antara emotional labor dengan kepuasan kerja pada guru di perguruan F. Tandean Tebing Tinggi. Subjek penelitian dari penelitian ini sebanyak 120 guru di Sekolah F. Tandean Tebing Tinggi. Penelitian kuantitatif ini menggunakan kuesioner dalam pengumpulan data. Uji asumsi yang dilakukan terdiri dari uji normalitas dan uji linearitas. Metode analisis data yang digunakan adalah teknik korelasi Product Moment dengan bantuan SPSS Statistic 25 for Windows. Hasil penelitian menunjukkan bahwa adanya korelasi positif antara kepuasan kerja dengan emotional labor. Sumbangan emotional labor terhadap kepuasan kerja adalah sebesar 7,1 persen. Kesimpulan dari penelitian ini menunjukkan adanya hubungan positif antara emotional labor dengan kepuasan kerja pada guru diterima.Â Â